The Effectiveness of Awig-Awig as Customary Law in Balinese Culture (Case Study: The Coastal Areas and Plains) - W. Yulianingsih; Aldira Mara Ditta C. P.; Waluyo (Future Science)
This research aims to find that the regulation of Customary Law exists in written form. This research also wants to prove that the customs regulations in each region in Bali differ according to the customary habits of each region and the existence of these awig-awig is still there to adjust the needs of the community following the current situation. Awig-awig made as an effort to maintain order, peace between the members of the indigenous village community. The method used in this study begins with the identification of a variety of literature related to customary law in terms of problems that occur and challenges that must be faced by coastal and plain communities. Then arranged in such a way as to bring up the exact problem formulation which later can be comprehensively reviewed through field studies and direct observations specifically related to the problem taken in this research namely the application of awig-awig as written customary law. The results of this research are expected to be able to contribute positively to the socio-cultural situation in Balinese society.